Policy Integration and Multi-Level Governance: Dealing with the Vertical Dimension of Policy Mix Designs - Howlett, Michael; Vince, Joanna; Del Río, Pablo (Politics and governance, 2017)
Multifaceted problems such as sustainable development typically involve complex arrangements of institutions and instruments and the subject of how best to design and operate such ‘mixes’, ‘bundles’ or ‘portfolios’ of policy tools is an ongoing issue in this area. One aspect of this question is that some mixes are more difficult to design and operate than others. The paper argues that, ceteris paribus, complex policy-making faces substantial risks of failure when horizontal or vertical dimensions of policy-making are not well integrated. The paper outlines a model of policy mix types which highlights the design problems associated with more complex arrangements and presents two case studies of similarly structured mixes in the areas of marine parks in Australia and coastal zone management in Europe—one a failure and the other a successful case of integration—to illustrate how such mixes can be better designed and managed more effectively.